Tuning surface grafting density of CeO2 nanocrystals with near- and supercritical solvent characteristics. Issue 3 (17th December 2015) - Giroire, B.; Slostowski, C.; Marre, S.; Aymonier, C.; Aida, T.; Hojo, D.; Aoki, N.; Takami, S.; Adschiri, T.
Abstract : In this work, the solvent effect on the synthesis of CeO2 nanocrystals prepared in near- and supercritical alcohols is discussed. Abstract : In this work, the solvent effect on the synthesis of CeO2 nanocrystals synthesized in near- and supercritical alcohols is discussed. The materials prepared displayed a unique morphology of small nanocrystals (<10 nm) aggregated into larger nanospheres (∼100–200 nm). In such syntheses, alcohol molecules directly interact with the nanocrystal surface through alkoxide and carboxylate bondings. The grafting density was quantified from the weight loss measured using thermogravimetric analysis. A direct correlation between the grafting density and the alcohol chain length can be established. It was demonstrated that the shorter the alcohol chain length ( i.e. methanol), the higher the surface coverage is. This trend is independent of the synthesis mode (batch or continuous). Additionally, an influence of the grafting density on the resulting nanocrystal size was established. It is suggested that the surface coverage has a high influence on the early stages of the nucleation and growth. Indeed, when high surface coverages are reached, all surface active sites are blocked, limiting the growth step and therefore leading to smaller particles. This effect was noticed with the materials prepared in the continuous mode where shorter reaction time was performed.